Nurse prescribing in China: A systematic review - Cheng Li; Gunjeong Lee (The Asia Pacific Scholar)
Introduction: This study aims to explore the development of nurse prescribing and identify nurse prescribing implementation and challenges in China. Methods: Conducted as a systematic review adhering to the PRISMA, this study involved a comprehensive literature search across various databases. A timeline mapping and a region mapping were conducted. Results: A total of 28 articles from databases were included in the study. The growth of nursing education and research, the emergence of specialty nurses, and the establishment of nurse-led clinics have contributed to the advancement of nurse prescribing in China. Presently, approximately half of the 34 regions in China are either actively researching or preparing for nurse prescribing involving medication. Conclusion: Based on the findings, several tasks have been identified for the implementation of nurse prescribing in China. Firstly, it is imperative to elevate the overall level of nursing education and revise the existing curriculum to equip nursing students with the necessary knowledge and skills required for prescribing. Secondly, it is crucial to establish a systematic qualification system for prescribing nurses, defining the roles of specialty nurses and advanced practice nurses. Thirdly, the development of nurse prescribing includes scope of nursing practice and prescribing protocols are essential. Lastly, extension of the geographic reach of legislation and pilot projects is needed to realise the nationwide implementation of nurse prescribing.